Supervisory management - Mosley, Donald C. (South-Western Pub. Co., 2008)
Your best path to becoming a successful, effective supervisor begins with the practical knowledge, the many opportunities to develop your supervisory skills, and the solid understanding of management principles you will gain in Mosley, Mosley, and Pietri's SUPERVISORY MANAGEMENT. With understandable "hands-on" coverage, the authors inspire you--emphasizing a positive approach of working cooperatively WITH people to develop and empower you to better perform in a supervisory role. Including cutting-edge information throughout as well as real world cases and Skill Builders that help you practice what you are learning, the Seventh Edition of this best-selling text is an essential resource that you will turn to again and again as you progress in your supervisory career